Multiproxy analysis of permafrost preserved faeces provides an unprecedented insight into the diets and habitats of extinct and extant megafauna. (1st September 2021) - Polling, Marcel; ter Schure, Anneke T.M.; van Geel, Bas; van Bokhoven, Tom; Boessenkool, Sanne; MacKay, Glen; Langeveld, Bram W.; Ariza, María; van der Plicht, Hans; Protopopov, Albert V.; Tikhonov, Alexei; de Boer, Hugo; et al.
Abstract: The study of faecal samples to reconstruct the diets and habitats of extinct megafauna has traditionally relied on pollen and macrofossil analysis. DNA metabarcoding has emerged as a valuable tool to complement and refine these proxies. While published studies have compared the results of these three proxies for sediments, this comparison is currently lacking for permafrost preserved mammal faeces. Moreover, most metabarcoding studies have focused on a single plant-specific DNA marker region. In this study, we target both the commonly used chloroplast trn L P6 loop as well as nuclear ribosomal ITS (nrITS). The latter can increase taxonomic resolution of plant identifications but requires DNA to be relatively well preserved because of the target length (∼300–500 bp). We compare DNA results to pollen and macrofossil analyses from permafrost and ice-preserved faeces of Pleistocene and Holocene megafauna. Samples include woolly mammoth, horse, steppe bison as well as Holocene and extant caribou. Most plant identifications were found using DNA, likely because the studied faeces contained many vegetative remains that could not be identified using macrofossils or pollen. Several taxa were, however, identified to lower taxonomic levels uniquely with macrofossil and pollen analysis. The nrITS marker provides species level taxonomic resolution for commonly encountered plant families that are hard to distinguish using the other proxies (e.g. Asteraceae, Cyperaceae and Poaceae). Integrating the results from all proxies, we are able to accurately reconstruct known diets and habitats of the extant caribou. Applying this approach to the extinct mammals, we find that the Holocene horse and steppe bison were not strict grazers but mixed feeders living in a marshy wetland environment. The mammoths showed highly varying diets from different non-analogous habitats. This confirms the presence of a mosaic of habitats in the Pleistocene 'mammoth steppe' that mammoths could fully exploit due to their flexibility in food choice. Highlights: The first integrated analysis of DNA, pollen and macrofossils from permafrost faeces. Successful amplification of up to 28, 6 kyr old DNA using long, plant-specific nrITS. High taxonomic resolutions allow detailed insights in extinct megafaunal habitat. Macrofossils and DNA show diverse woolly mammoth diet and use of 'mammoth steppe'.